Strategic HRM The implications for pharmaceutical R&D - Jones, Oswald
The paper is concerned with the strategic human resource management (HRM) implications of recent pressure for change in the pharmaceutical industry : the mergers and marketing agreements which began in the late 1980s; Government attempts to control NHS spending through the 'Limited List'; and competition from generic drugs. Despite the increasing use of information technology and expert systems, scientific research remains highly labour intensive and very costly. However, the continued success of all the leading pharmaceutical companies is heavily dependent upon the ability of R&D to innovate new drugs.
The research establishes that there has been a switch from personnel management to HRM in the pharmaceutical industry. This change is symbolized by a 'hardening-up' of the personnel function as 'welfare issues' give way to a more business-centered approach to employee relations. In addition, first line managers (FLMs) are taking greater responsibility for the appraisal and reward of their own staff. The research also establishes that leading pharmaceutical companies no longer regard R&D as a core activity and this represents their desire to improve efficiency and reduce R&D spending. The extent to which the core-periphery model has had an impact on employment contracts of R&D staff varies between firms in the sample. Three companies rejected the use of fixed-term contracts while in the other three companies such arrangements were viewed much more favourably. However, there was certainly a consistent trend towards the sub-contracting of some R&D activities. In each of the companies R&D employees were encouraged to become less insular and more aware of the commercial aspects of the business. The study also confirmed the widely-held view that HRM decisions are not regarded as strategic issues : only one company had an HR professional on the main board.
It is argued that the changes identified in the research pose a serious threat to the unique position of pharmaceutical companies in the UK economy. The strength of UK pharmaceutical companies has been based on their ability to maintain a long-term perspective with regard to R&D investment. The trends identified in this research are not irreversible, but it is clear that the value of in-house R&D is being questioned at the highest levels within the pharmaceutical industry.
This paper covers the strategy of Human Resource Management (HRM) in the pharmaceutical industry and the swing from Personnel Management to HRM. It reports that despite increased use of information technology and expert systems, scientific research is still highly labour intensive and costly, whilst research and development is no longer regarded as a core activity.
Keywords: Strategic HRM; Pharmaceutical R&D.